The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.15713/ins.jmrps.159
|View full text |Cite
|
Sign up to set email alerts
|

Determination of different positioning errors in digital panoramic radiography: A retrospective study

Abstract: Aim: This study aims to determine the different positioning errors in digital panoramic radiographs in a sample of records collected from the department of oral medicine and radiology. Materials and Methods: The study consisted of 500 panoramic radiographs obtained from the Department of Oral Medicine and Radiology, AME's Dental College and Hospital, Raichur, was taken serially (from the year January 2019), and was retrospectively assessed for positioning errors. These positioning errors were assessed by two o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In the present study, the second most common error was head turned to one side as 14.5%. In the study by Kattimani et al the error of head turn to one side was found to be 30.8% (34), and the finding was correlated with that reported in the study by Khotor et al stating the error as 33.8% (35). In our study, the third most common error was chin tipped low as 13.3% (n=121).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the second most common error was head turned to one side as 14.5%. In the study by Kattimani et al the error of head turn to one side was found to be 30.8% (34), and the finding was correlated with that reported in the study by Khotor et al stating the error as 33.8% (35). In our study, the third most common error was chin tipped low as 13.3% (n=121).…”
Section: Discussionsupporting
confidence: 90%
“…The third most common error in this study was the head being rotated towards one side seen in 16.4% which caused asymmetrical condyle and ramus 9,[16][17][18] . In comparison with other studies, it was found that this error was in a similar range to one adult study (17.4%) 6 .…”
Section: Discussionmentioning
confidence: 71%
“…The least common error was patient movement during exposure which caused blurring on the radiograph and also step defects on the inferior border of the mandible 5,6,16,18,19 . Children and adolescents may not remain quiet and motionless during the panoramic procedures and movement errors could be more prevalent among our study group.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Among all the positional errors mentioned above, the most common error is the failure to keep the tongue against the palate. [24][25][26] Due to the failure of holding the tongue against the palate, the palatoglossal airspace (PGA) appears in panoramic radiographs as a dark radiolucent band under the hard palate and on the apices of the anterior maxillary teeth. 27,28 This artefact significantly reduces the quality of the panoramic radiograph as it may be difficult or impossible to interpret the desired periapical region for correct diagnosis and treatment planning (for example, making it difficult to interpret cystic lesions in the anterior area of the upper jaw).…”
Section: Introductionmentioning
confidence: 99%
“…The typical patient positioning errors in PR include failure to rest the tongue against the palate, head positioned forward, head positioned backward, head twisted towards the left or right, head tilted to the left or right, the chin too high, the chin too low, a slumped position and inadequate neck extension, not resting the chin on the chin support, failing to use the bite guide, lips opened, patient movement during imaging and not removing the metal objects or prostheses 21–23 . Among all the positional errors mentioned above, the most common error is the failure to keep the tongue against the palate 24–26 …”
Section: Introductionmentioning
confidence: 99%